2016
DOI: 10.1002/slct.201601853
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Dialkylhydroxybenzoates with Unusual Structures: First Example of a Discrete Three‐Blade Paddle‐Wheel and a Solvent Engulfed Coordination Polymer

Abstract: Sterically encumbered 4‐hydroxy‐3,5‐diisopropylbenzoic acid (H2diphba), bearing a carboxylic acid, a phenol and two iso‐propyl substituents, has been investigated for the first time as a ligand and supramolecular synthon to isolate eight Zn(II) complexes, [Zn2(Hdiphba)3(OAc)(L)] (L=DMF(1) or pyz (2)), [Zn(Hdiphba)2(2,2′‐bpy)] (3), [Zn(Hdiphba)2(1,10‐phen)] (4), [Zn(Hdiphba)2(pz)2] (5) and [Zn2(Hdiphba)2(μ2‐dmpz)2(Hdmpz)2] (6), [Zn(Hdiphba)2(4,4′‐bpy)]n⋅4nCH3OH (7.4nCH3OH), [Zn2(Hdiphba)4(4,4′‐azobpy)(H2O)2] (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…These findings were consistent with widely reported fact that thiadiazole-derived ligands may demonstrate versatile coordination modes which strongly depend on the presence of additional substituents [8,[22][23][24]. This diversity is particularly high in case of the coordination to Cu(II) and Zn(II) ions, which are well-known for their ability to adopt a wide variety of coordination modes [25,26].…”
Section: Introductionsupporting
confidence: 90%
“…These findings were consistent with widely reported fact that thiadiazole-derived ligands may demonstrate versatile coordination modes which strongly depend on the presence of additional substituents [8,[22][23][24]. This diversity is particularly high in case of the coordination to Cu(II) and Zn(II) ions, which are well-known for their ability to adopt a wide variety of coordination modes [25,26].…”
Section: Introductionsupporting
confidence: 90%
“…It should be noted that only a few examples of Cu(II) paddle‐wheel complexes are reported in which axial and equatorial positions serve as the point of extension through intermolecular interaction ,. We are particularly interested in investigating systems of dinuclear Cu(II)‐carboxylates of structurally bifunctional ligand, 4‐hydroxy‐3,5‐diisopropyl benzoic acid (H 2 diphba, Scheme ) . H 2 diphba contains two functional groups, ‐COOH and –OH, placed diagonally opposite to each other on the benzene ring.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the cavities formed in the extended networks can encapsulate potentially important solvent clathrates/guest molecules. By using H 2 diphba, we have earlier shown that Zn(II)‐Hdiphba complex encapsulates methanol tetramer which is a prominent species in methanol vapour ,…”
Section: Introductionmentioning
confidence: 99%